DETERMINAN EKSPOR CRUDE PALM OIL (CPO) INDONESIA, MALAYSIA DAN THAILAND - Tencau, Vedriana; Kurniasih, Erni Panca (KINDAI, 2024)
Abstract: The aim of this research is to test and analyze the impact of crude palm oil (CPO) exports in the three countries producing and the world's largest exporters of CPO, namely Indonesia, Malaysia and Thailand. Observations were carried out on five independent variables namely Production, Exchange Rate, Inflation, International Prices and World CPO Consumption with the dependent variable being CPO exports. As for the observation period from 2008 to 2022 in the final annual report. The study used quantitative descriptive analysis of panel data regression with the Vector Error Correction Model (VECM) method to determine long-term and short-term effects. Statistical data processing utility using the eviews10 application. The results of data analysis show that production, inflation and prices in the long term have an influence on exports, while exchange rate and consumption have no influence. In the short term, production and consumption have an influence while exchange rates, inflation and prices have no influence on exports. Keywords: CPO, Export, VECM